Inclusive landscape management plan for the transformation of the agrifood system in Rubyiro Sub Catchment, Rwanda - Uwanyirigira, D.; Musana, B.; Atampugre, Gerald; Tilahun, Seifu A.; Oke, Adebayo; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
Inclusive landscape management (ILM) is a holistic approach to managing landscapes that considers the needs of all stakeholders, including local communities and people with disabilities. This Inclusive Landscape Management Plan (ILMP) seeks to provide a framework for the sustainable management and development of landscapes in the Rubyiro sub-catchment of Rwanda. The ILMP is designed to address the increasing pressure on landscapes in Rwanda from deforestation, land degradation, poor water management, unsustainable mining and climate change. The ILMP emphasizes the integration of social and ecological systems, local participation and sustainable resource use and management within landscapes. It is a response to ‘top-down’ approaches to sustainable development, in which power and decision-making are in the hands of external development professionals. Instead, the ILMP is based on shared ownership of decision-making and the full participation of all stakeholders.